Paying the Professoriate: Trends in India - Jayaram, N. (International Higher Education, 2012)
Academic salaries in India have recently been significantly improved. Yet, these raises have not been accompanied by higher standards of teaching or research. This article focuses on the realities of Indian higher education as they relate to academic salaries and contracts.